Metabolomics based inferences to unravel phenolic compound diversity in cereals and its implications for human gut health - Tiozon, Rhowell Jr. N.; Sartagoda, Kristel June D.; Serrano, Luster May N.; Fernie, Alisdair R.; Sreenivasulu, Nese (Elsevier, 2022)
Whole grain cereals are a good source of nutrients. Several cutting-edge metabolomic platforms have been deployed to identify various phenolic compounds and enhance cereal bioactive bioavailability. A diet rich in cereal phenolics may modify the microbial composition, support gut homeostasis, and increase gut health, thereby lowering the risk of non-communicable illness. In this work, we reviewed current metabolomic breakthroughs in cereal phenolic profiling and their effects on human health via gut microbiota modulation. We argue that the information presented in this paper will assist in the development of nutritionally superior cereal breeds and functional foods. Most cereal grains contain ferulic acid derivatives, caffeoyl glycerides, and feruloyl and coumaroyl esters. While there has been significant progress in discovering novel phenolic compounds in cereals, quantifying these molecules, and translating their therapeutic effects from animal model systems to humans remains a challenge. To this end, metabolomics, and other high-throughput-omics-based platforms must be integrated to further examine the structure and functionality of phenolic metabolites to breed nutritionally rich cereals as well as map their influence on human health benefits. Rare alleles must be introduced to improve bioactive content in cereal grains while maintaining yield. Following that, these exceptional varieties must be effectively processed to maximize phenolic bioavailability.